On Freud's "Negation" - O'Neil, Mary Kay; Akhtar, Salman, 1946 July 31- (Contemporary Freud., 2011)
Ever since Freud proposed that certain ideas can be permitted to become conscious only in their inverted and negative forms, interest has grown into the entire realm of the presence of absence, so to speak. Or, perhaps, it is better to term such mental contents as the presence in the form of absence. These two ways of conceptualizing Freud's negation have led to a panoply of ideas that include negative hallucination, psychic holes, negative narcissism, selfishly motivated erasure of the Other, and the so-called "work of the negative". This volume elucidates these concepts and refines the disti.